Tabib Family’s Role on Fracture Treatment in Aceh, 1950-2020: A Historical Reconstruction - Teuku Kusnafizal; Abdul Azis; Sufandi Iswanto (Indonesian Historical Studies, 2020)
This research traces the origin of traditional fracture treatment, and identifies the values of local wisdom, especially in traditional healing process performed by the tabib family and to describe how the traditional healing system is developed from ancient times to the present. This study used a qualitative approach and historical methods through topic selection, heuristics or collecting sources, verification or source criticism, and sources and historiography interpretation. Based on the research that has been conducted, the following results were obtained: (1) Fracture treatment has been performed since 1950 in Aceh, especially among the tabib family coming from South Aceh through the inheritance of knowledge from generation to generation; (2) The regeneration process was performed in the healer family, in this case the father inherited from his children or grandparents to his grandchildren to study this knowledge, and practiced it in their entire life; (3) Entering the modern era, traditional medicine has developed in several aspects, so, people tend to believe in this treatment. This study is a part of the historical local wisdom (HLW) to determine how the development of traditional medicine in Aceh from time to time.